Towards developing a universal influenza vaccine - Palese, Peter (Henry Stewart Talks, 2018)
The challenge of developing influenza vaccines, What is a universal influenza vaccine and how feasible is it?, Current achievements and problems in the development of a universal influenza vaccine, The problem of predicting efficacy of universal vaccines and the limits of model animals